Phenylene Bridged Cyclic Azaacenes: Dimers and Trimers. Issue 27 (12th March 2018) - Hahn, Sebastian; Koser, Silke; Hodecker, Manuel; Seete, Pascal; Rominger, Frank; Miljanić, Ognjen Š.; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: The synthesis and characterization of novel macrocyclic, phenylene‐bridged azaacenes is reported. These species were obtained either by a conventional benzoin– diamine condensation, as shown for the case of the cyclotrimers, in which the azaacene units are separated by meta ‐connected phenylene bridges, or by a Buchwald–Hartwig‐type Pd‐catalyzed coupling, which employs 1, 2, 5, 6‐tetrabromodibenzocyclooctatetraene as the substrate and bis‐TIPS‐ethynylated diaminobenzene, ‐naphthalene or ‐anthracene as the coupling partner to give the double coupling products azaacene‐annulated dibenzocyclooctatetraenes in moderate yields. The macrocycles show strong emission and light emitting diodes have been built with brightnesses exceeding 1600 cd m −2 . We evaluated the optical and electronic properties and the solid‐state structures of the molecules and discuss their properties through comparison with their linear and tetrameric N‐heteroacene counterparts. Abstract : Bright and colourful : Different macrocyclic, phenylene‐bridged azaacenes were obtained by condensation reations and Buchwald–Hartwig‐type couplings in a two step synthesis. We evaluated the optical and electronic properties, use the targets as emitting materials in OLEDs and discuss their properties through comparison with their linear and tetramer N‐heteroacene counterparts.